Exploring Human Natures in The Contemporary Society through the Representation of the Characters in The Little Prince Novel - Satria Aji Saputra; Imas Istiani (Universitas Negeri Semarang, 2026)
This study aims to examine how the various characters encountered by the protagonist in The Little Prince are portrayed. This is done with the aim of exploring the underlying meaning of these interactions and their reflection on Lacanian psychoanalysis. Specifically, this paper applies Jacques Lacan's psychoanalytic model, comparing the characters and their actions based on his three main registers, including Imaginary, Symbolic, and Real. This research paper uses a qualitative research approach related to textual analysis. This is done through close reading, character analysis, and direct application of Lacanian theory, using excerpts from the novel as primary evidence. The results show that the characters' actions and dialogues are representative of the psychological situations and deficiencies of contemporary adult society. Furthermore, the consequences of the protagonist's interplanetary journey in The Little Prince demonstrate profound psychological movements, the shock of Imagination, the disintegration of the Symbolic order, and a final encounter with the existential emptiness of Reality on the planet. Ultimately, this study is a critical reflection, and encourages adults to question the values ​​and principles accepted in society that they have adopted in contemporary life.